The Use of the Armenian Stress. Directions of Linguistics and Levels of Language Analysis as a Context of Contestation - Karapetyan, Mariam (Bulletin of Yerevan University B: Philology, 2024)
The article discusses the need to update the view on one of the important areas of linguistics - punctuation issues, using the example of the use of stress. The fact that the requirement of mandatory or often practically "voluntary-mandatory" stress is perplexing can be seen by familiarizing oneself with the arguments of a number of Armenian linguists, especially with the theories of many foreign linguists who have developed countless clarifying logics on issues related to language. The subject of this article is the possible contribution of some modern linguistic theories in the use of stress, as well as in understanding the functions of punctuation in general. The statements of Armenian and foreign linguists considered in the article create a range of approaches, in comparison with which it is possible to discuss the rules of using punctuation marks and, in particular, stress. The article is an attempt to highlight some landmarks from world linguistics that will help us be bolder in finding solutions to the actual problems of the Armenian language.